An Agent-Based Auction Protocol on Mobile Devices - Yu-Fang Chung; Tzer-Long Chen; Tzer-Shyong Chen; Dai-Lun Chiang; Yu-Ting Chen (Journal of Applied Mathematics)
This paper proposes an English auction protocol to preserve a secure, fair, and effective online auction environment, where the operations are integrated with mobile agent technology for bidders participating in online auctions. The protocol consists of four participants, namely, registration manager, agent house, auction house, and bidder.